Surgical Site Infections Complicating the Use of Negative Pressure Wound Therapy in Renal Transplant Recipients. (24th September 2019) - Lam, Susanna; Lau, Ngee-Soon; Laurence, Jerome Martin; Verran, Deborah Jean
Abstract : Surgical site infections (SSI) of the abdominal wall in renal transplant recipients can on occasion require management with negative pressure wound therapy (NPWT). This is often successful, with a low risk of further complications. However, we describe three cases in which persistent or recurrent surgical site sepsis occurred, whilst NPWT was being deployed in adults with either wound dehiscence or initial SSI. This type of complication in the setting of NPWT has not been previously described in renal transplant recipients. Our case series demonstrates that in immunosuppressed transplant recipients, there may be ineffective microbial or bacterial bioburden clearance associated with the NPWT, which can lead to further infections. Hence recognition for infections in renal transplant patients undergoing treatment with NPWT is vital; furthermore, aggressive management of sepsis control with early debridement, antimicrobial use, and reassessment of the use of wound dressing is necessary to reduce the morbidity associated with surgical site infections and NPWT.